Ethylene carbonate and polyethylene glycol as efficient plasticizers in CMC-PVA-NH4NO3-based polymer electrolyte - Noor Saadiah, Mohd Ali; Nagao, Yuki; Ahmad Salihin, Samsudin (DRPM Universitas Indonesia, 2020)
This study deal with the investigation of the influence of plasticizer (PEG and EC) on ionic conduction of CMC-PVA-NH4NO3. Blended biopolymer electrolytes (BBEs) based on carboxymethyl cellulose-polyvinyl alcohol (CMC-PVA) doped with ammonium nitrate (NH4NO3) were obtained via casting technique incorporating with polyethylene glycol (PEG) and ethylene carbonate (EC) which were act as plasticizer. Electrical impedance spectroscopy (EIS) was used to evaluate the effect of plasticization on the ionic conduction properties. The ionic conductivity was improved from 1.70 x 10-3 S/cm for un-plasticized BBEs to 3.92 x 10-3 S/cm for plasticized BBEs with EC and 3.00 x 10-3 S/cm for plasticized BBEs with PEG. The improvement was corresponding to ability of plasticizer to weaken the Columbic force and promote further dissociation in the ionic dopant. The highest ionic conductivity was achieved for BBEs plasticized with EC hence suggesting the suitability of EC as plasticizer in this present system The BBEs system showed the Arrhenius characteristic at elevated temperature and demonstrating increasing ionic conductivity. Dielectric properties of all BBEs system was found to improve upon addition of EC and PEG and demonstrating their correlation with the trend in conductivity.